Review of the genus Agonochaetia Povolný (Lepidoptera, Gelechiidae), and description of a new genus and species from the Canary Islands - Landry, Jean-François; Nazari, Vazrick; Bidzilya, Oleksiy; Huemer, Peter; Karsholt, Ole (Zootaxa, 2017)
The Holarctic genus Agonochaetia is reviewed and a new species, Agonochaetia shawinigan Landry, sp. nov. is described from Québec, Canada. In addition, a new glandiductor-bearing genus and species, Canarischema fuerteventura Karsholt, gen. nov., sp. nov. is described from the Canary Islands. Comparative diagnoses, a key to species, illustrations of external aspect, male and female genitalia are provided for all species. Most species of Agonochaetia are rarely collected and known only from their types or from very few specimens. DNA barcodes are provided for four of the species from which DNA was recovered. Analysis of DNA barcodes suggests that Agonochaetia may be paraphyletic. Phylogenetic relationships to other Gnorimoschemini genera bearing a pair of glandiductors above the phallus are discussed.